2018
DOI: 10.1155/2018/6828396
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Necrosis, Pseudoprogression, Pseudoresponse, and Tumor Recurrence: Imaging Challenges for the Evaluation of Treated Gliomas

Abstract: Glioblastoma (GBM) is the most common primary malignant type of brain neoplasm in adults and carries a dismal prognosis. The current standard of care for GBM is surgical excision followed by radiation therapy (RT) with concurrent and adjuvant temozolomide-based chemotherapy (TMZ) by six additional cycles. In addition, antiangiogenic therapy with an antivascular endothelial growth factor (VEGF) agent has been used for recurrent glioblastoma. Over the last years, new posttreatment entities such as pseudoprogress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
145
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(157 citation statements)
references
References 61 publications
4
145
1
7
Order By: Relevance
“…A post-RT decrease in mode_ADC_FLAIR was significantly lower in those showing pseudoprogression compared with those who went on to show true early progression in our study. While pseudoprogression is well-documented in adult gliblastomas treated with RT + TMZ, typically seen within the first 3 months after radiation, 33 there are very few reports on DIPG. Chassot et al 34 reported 4/22 (18%) cases of pseudoprogression in children with DIPG treated with RT + TMZ and found no difference in overall survival between pseudoprogression and true progression cases.…”
Section: Discussionmentioning
confidence: 99%
“…A post-RT decrease in mode_ADC_FLAIR was significantly lower in those showing pseudoprogression compared with those who went on to show true early progression in our study. While pseudoprogression is well-documented in adult gliblastomas treated with RT + TMZ, typically seen within the first 3 months after radiation, 33 there are very few reports on DIPG. Chassot et al 34 reported 4/22 (18%) cases of pseudoprogression in children with DIPG treated with RT + TMZ and found no difference in overall survival between pseudoprogression and true progression cases.…”
Section: Discussionmentioning
confidence: 99%
“…Considering previous work showing that the ratio of [1-13 C]glycine to total HP signal (γ-glutamyl-[1-13 C]glycine plus [1-13 C]glycine) is positively correlated with GGT activity 31 , previous studies showing higher levels of GGT in U87 glioma cells compare to normal brain 19 , and our observation that higher HP [1-13 C]glycine production in tumor was associated with higher GGT expression in tumor tissue, our results collectively point to the potential of γ-glutamyl-[1-13 C]glycine as a HP probe to detect brain tumor in vivo in real time. Furthermore, tumor therapy, and in particular radiation, can lead to "pseudoprogression" -MRI changes that cannot easily distinguish between tumor recurrence and treatment effects [58][59][60] . Because HP γ-glutamyl-[1-13 C]glycine detects a molecular event specific to tumor, it could also help in evaluating treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of PET/CT in this kind of patients and of molecular imaging more in general is to assess metabolically active lesions that are not necessarily evident on structural MRI [33]. In fact, on follow-up imaging it cannot clearly distinguish between recurrence and necrosis whereas PET, providing in vivo metabolic information, will show intense metabolic activity in case of recurrence and photopenia or reduced uptake of the tracer in the interested region in case of radiation necrosis [34].…”
Section: Diagnostic Imaging and Nuclear Medicine In Brain Tumorsmentioning
confidence: 99%